PEMBANGUNAN INDUSTRI PERFILMAN BALI DENGAN KONSEP BEKERJA TULUS IKHLAS KHAS KEARIFAN BALI YANG BERNILAI EKONOMIS - Bagus Kesuma Yudha, Anak Agung Ngurah (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
The film industry in Indonesia has entered a good period. After going through a phase of ups and downs with diverse film themes in the archipelago, slowly, film education qualifications increase to lead to a self-reliant industry. Indonesia is not only geographically and culturally diverse. Here, Indonesia has become very diverse from existing film ideas. Time passed and there was an increase in the film industry focused on one point / area which happened to be the center of Indonesian government, Jakarta. After becoming an industry reference accompanied by a lot of film education, Jakarta became a role model. Trends are emerging in the Jakartasentris area. All started from the center. But somehow, Bali, despite having a relief movement, is still unable to industrialize cinematographic works like Jakarta. In this article, we will further review the picture of the film industry in Bali and the rotation of the economic value in the film industry in Bali. The research method used is descriptive qualitative research method. Where this method is based on the philosophy of postpositivism, it is used to examine the condition of natural objects, and researchers are the key instruments. Data collection techniques are triangulated, data analysis is inductive or qualitative, and the results emphasize meaning rather than generalization.